Reliability Analysis of Dynamic Buckling Stiffened Panels. (2016) - Ouadia, Mouhat; Abdellatif, Khamlichi
Abstract: The stiffened panels are often forming less thin wall. Consequently, the dynamic buckling is a major challenge to be addressed in the quest to increase the strength-to-weight ratio. Stiffened are subjected to various loading conditions can be static or dynamic, as they may suffer from degradation of the material and initial geometric distortions due to the welding assembly process used. Buckling of structures subject to sudden dynamic impulse load can be analyzed without detour to the approach based on the equations of motion. In this approach, which can be easily adapted to the methods of calculation using the finite element method, the motion equations are solved for various values of the parameters defining the loading. The value of the load parameter for which there is a big change in the response then defines the critical load according Budiansky and Roth criterion. In this work, dynamic buckling of stiffened panels is analyzed numerically through a nonlinear incremental formulation using explicit time integration procedure under Abaqus software package. The dynamic buckling state is recovered from the curve giving the end-shortening as function of time when the structure is subjected to a compressive rectangular pulse loading applied parallel ally to the stiffeners direction. Fixing the pulse duration and the initial distortion magnitude as well as the ratio of material degradation in the heat affected zone, the dynamic buckling load was identified for each given configuration. This process has enabled the derivation of a response surface model which was used with Monte Carlo method to determine reliability of the stiffened panel with regards to the dynamic buckling state.